Composite powder, metal anti-corrosion coating composition and preparation method thereof and metal anti-corrosion method

Through the in-situ self-assembly process of MOF/GO composite powder, a metal anti-corrosion coating with self-healing and barrier synergistic effects was prepared, which solved the problem of micro-cracking of traditional coatings in complex environments, achieved efficient anti-corrosion performance and simple preparation process, and is suitable for shipping, bridges, industrial pipelines, automobiles and building structures.

CN120648278APending Publication Date: 2025-09-16SHANGHAI ZHONGCAI ENG DETECTION CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510784653.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing metal anti-corrosion coatings are prone to microcracks in complex environments such as long-term alternating wet and dry conditions and temperature cycles. Traditional multi-layer coating systems do not provide continuous protection. The microcapsule self-repair strategy has complex processes and poor interface compatibility. The dispersibility and barrier properties of single MOF powders are limited, making it difficult to achieve a balance between long-term barrier properties, continuous protection, and simplicity of on-site processes.

Method used

MOF/GO composite powder is prepared through an in-situ self-assembly process. The MOF pore release and GO barrier toughening are combined to form a coating with a stable pore structure. The metal ions are quickly released and the organic ligands form a passivation layer. The GO network delays the diffusion of corrosive media, achieving a synergistic effect of self-repair and barrier.

Benefits of technology

It achieves rapid self-repair under salt spray and mechanical damage conditions, improves the mechanical toughness and barrier properties of the coating, is suitable for industrial large-scale production, and has long-term and reliable multi-environment protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005446750520000061
    Figure BDA0005446750520000061
Patent Text Reader

Abstract

The invention discloses composite powder, a metal anti-corrosion coating composition, a preparation method of the metal anti-corrosion coating composition and a metal anti-corrosion method. Zn < 2 + > and imidazole ligands are self-assembled on the surface of GO in situ in DMF to prepare composite powder with stable pore channels and barrier and self-repairing functions, and the composite powder is dispersed in an epoxy matrix to prepare the coating. When the coating is damaged, the MOF releases Zn < 2 + > to form a passive film with the ligand, and the GO network delays medium diffusion and enhances mechanical properties. And the coating has remarkable salt mist resistance and self-repairing performance, and is suitable for corrosion prevention of metals such as steel, aluminum-magnesium alloy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal anti-corrosion coatings, and in particular to a self-repairing active metal anti-corrosion coating based on in-situ composite of metal organic framework (MOF) and graphite oxide (GO), and a preparation and application method thereof. Background Art

[0002] Metal materials are widely used in shipping, bridges, industrial pipelines, automobiles, and building structures due to their excellent mechanical strength, processability, and cost-effectiveness. However, once exposed to corrosive environments such as oxygen-containing atmospheres, marine salt spray, and acidic and alkaline media, metal surfaces are prone to oxidation, pitting, and crack propagation, ultimately leading to decreased structural performance, increased maintenance costs, and even serious safety accidents. To slow the corrosion process, traditional anti-corrosion strategies mainly include:

[0003] First, multi-layer coating systems based on barrier and passivation principles are the most commonly used. Zinc-rich primers and micaceous iron primers can form a zinc- or iron-rich sacrificial protective layer on the substrate surface, blocking the corrosive medium through anodic sacrificial or passivation products. However, these multi-layer systems are prone to microcracks within the coating under complex conditions such as long-term alternating wet-dry cycles and temperature cycling. Once the corrosive medium penetrates, it spreads rapidly, making it difficult to achieve sustained and effective protection.

[0004] Secondly, in recent years, microencapsulation technology has been applied to self-healing coatings. Corrosion inhibitors and repair agents are encapsulated in microcapsule shells. When the coating is damaged, the internal microcapsules rupture and release active substances, forming a passivation film on the damaged area. While this active repair strategy can slow the spread of corrosion, its preparation relies on a multi-step emulsification, coating, and drying process, which is complex and costly. Furthermore, the interfacial compatibility between the microcapsules and the substrate is poor, which can easily lead to capsule agglomeration and uneven dispersion, affecting the overall performance of the coating.

[0005] Additionally, self-healing coatings based on metal-organic frameworks (MOFs) are gaining attention. MOFs possess a regular, tunable pore structure that can store metal ions or organic ligands. These ions are released upon coating damage or corrosive media stimulation, generating in situ passivation products. However, the dispersibility and barrier properties of single MOF powders in resin matrices are limited, making them ineffective in improving the mechanical toughness and sealing properties of coatings.

[0006] In summary, traditional barrier or passivation coatings and single active repair strategies each have their advantages and disadvantages, but it is difficult to achieve a balance between long-term barrier performance, sustained protection, and ease of on-site processing. There is an urgent need for a new anti-corrosion coating that combines active self-repair and passive barrier functions, has a simple preparation process, and is easily commercializable. Summary of the Invention

[0007] To overcome the shortcomings of the aforementioned prior art, the present invention provides a self-healing active metal anti-corrosion coating based on a MOF / GO composite powder. Combining the synergistic effects of MOF pore release and GO barrier toughening, the highly efficient composite powder is prepared through a simple in-situ self-assembly process and dispersed in an epoxy matrix. This results in a metal anti-corrosion coating with a stable pore structure, excellent barrier properties, and scratch self-repair capabilities. Under conditions of salt spray and mechanical damage, the coating rapidly releases metal ions and organic ligands to form a passivation layer. Simultaneously, the GO network slows the diffusion of corrosive media, achieving long-term, reliable protection in multiple environments.

[0008] In a first aspect, the present invention provides a composite powder comprising:

[0009] Zeolite-like metal-organic frameworks are self-assembled by divalent zinc ions and imidazole organic ligands.

[0010] Graphite oxide, with a degree of oxidation of 35 to 45 at%;

[0011] The zeolite-like metal organic framework and the graphite oxide are compounded by in-situ self-assembly to form a composite powder with a stable pore structure, barrier properties and self-repairing function.

[0012] In some technical solutions, the mass ratio of the zeolite-like metal organic framework to graphite oxide is 1:0.5 to 1:5.

[0013] In some technical solutions, the zeolite-like metal organic framework has a crystal size of 50 to 200 nm; and / or,

[0014] The average sheet size of the graphite oxide is 0.5 to 5 μm; and / or,

[0015] The specific surface area of ​​the composite powder is not less than 600m 2 / g.

[0016] In some technical solutions, the imidazole organic ligand is selected from 2-methylimidazole or a substituted imidazole thereof;

[0017] The oxygen functional groups contained in the graphite oxide are selected from hydroxyl groups, epoxy groups or carboxyl groups, and the total content of the oxygen functional groups is 20 to 45 wt %.

[0018] In a second aspect, the present invention further provides a method for preparing the composite powder, comprising the following steps:

[0019] dispersing graphite oxide in a suitable solvent to prepare a dispersion;

[0020] preparing a divalent zinc salt solution and an imidazole organic ligand solution in a suitable solvent to obtain a zinc ion solution and a ligand solution;

[0021] The dispersion, zinc ion solution and ligand solution are mixed and an in-situ self-assembly reaction is carried out in the same reaction system, so that the divalent zinc ions and the imidazole organic ligands are assembled on the surface of the graphite oxide to form a zeolite-like metal organic framework and composite with the graphite oxide;

[0022] The reaction products are separated, washed and dried to obtain a composite powder with a stable pore structure, barrier properties and self-repairing function.

[0023] In some technical solutions, the solvent is N,N-dimethylformamide, ethanol, water or a mixed solvent thereof; and / or,

[0024] Graphite oxide is added to a solvent at 0.1 to 10 wt %, and is ultrasonically treated for 5 to 15 minutes to obtain uniform dispersion; and / or,

[0025] The zinc ion solution is prepared from zinc nitrate, zinc acetate or zinc chloride, with a concentration of 0.05 to 0.5 mol / L; and / or,

[0026] The ligand solution is prepared from 2-methylimidazole or a substituted imidazole thereof, with a concentration of 0.1 to 1.0 mol / L; and / or,

[0027] Mixing the dispersion, zinc ion solution and ligand solution in a mass ratio of 1:(0.1-1):(0.5-5); and / or,

[0028] The in situ self-assembly reaction is carried out at 50-70° C. and normal pressure for 18-24 hours.

[0029] In a third aspect, the present invention further provides a metal anti-corrosion coating composition, comprising:

[0030] Epoxy solution, prepared from epoxy resin, with a content of 75 wt%;

[0031] The composite powder or the composite powder prepared by the above-mentioned preparation method has a content of 0.25 to 5 wt % based on the total mass of the coating composition.

[0032] In a fourth aspect, the present invention further provides a method for preparing the above-mentioned metal anti-corrosion coating composition, comprising the following steps:

[0033] Mixing epoxy resin and organic solvent in a container at a mass ratio of 2:1 to 4.5:1 to prepare a uniform epoxy solution;

[0034] adding the composite powder to the epoxy solution to obtain a uniform mixed solution;

[0035] The mixed liquid is subjected to a degassing treatment to obtain the metal anti-corrosion coating composition.

[0036] Some technical solutions further include adding a curing agent after the epoxy solution is prepared, and the mass ratio of the curing agent to the epoxy resin is 0.5:1 to 1.5:1.

[0037] In a fifth aspect, the present invention further provides a metal anticorrosion method, comprising:

[0038] The metal anticorrosion coating composition according to claim 7 is evenly applied to the surface of the metal substrate to be protected by brushing, spraying or dipping at a wet film thickness of 50-200 μm, wherein the metal substrate is steel, aluminum alloy or magnesium alloy;

[0039] It is then cured at 80-120°C for 1-3 hours to form an anti-corrosion coating with a stable pore structure, barrier properties and self-repairing function.

[0040] The coating of the present invention exhibits the following properties by dispersing ZIF-8 / GO composite powder in epoxy matrix:

[0041] Beneficial effects:

[0042] 1. The ZIF-8 pores of the present invention release Zn at the damaged part of the coating 2+ Combined with the organic ligand Hmim, zinc oxide and an organic passivation film are rapidly generated in situ to seal the metal surface; the GO layered structure and the epoxy network form a dense barrier layer, effectively delaying the diffusion of moisture, oxygen and corrosive ions, and significantly improving the salt spray resistance of the coating.

[0043] 2. In the microcrack area generated by mechanical stress or corrosive media, the MOF pores rupture and release active substances, forming a filling and passivation composite layer to restore the integrity of the coating; this process does not require external stimulation and can be automatically repeated.

[0044] 3. The GO sheets of the present invention are well dispersed in the epoxy matrix, improving the tensile and impact resistance of the coating, inhibiting crack propagation and increasing the rupture strength of the coating.

[0045] 4. The present invention adopts a one-step in-situ self-assembly method to prepare the composite powder, and directly adds it to the epoxy solution, without the need for multi-step microencapsulation or additional surface coating treatment, and is suitable for industrial large-scale production.

[0046] 5. The preparation of the composite powder and the curing of the coating of the present invention are carried out under normal pressure and medium temperature conditions. The process temperature control is simple and can meet the needs of on-site construction and industrial preparation.

[0047] In summary, the coating of the present invention takes into account barrier, protection, self-repair and mechanical properties, showing excellent comprehensive performance and high practical application value. DETAILED DESCRIPTION

[0048] The present invention is described below with reference to specific examples. The raw materials and equipment used in the examples are conventionally available, and the data and parameters are for demonstration only and should not be regarded as limiting the scope of protection of the present invention.

[0049] Example 1 (Preparation of ZIF-8 / GO composite powder)

[0050] 5 wt% graphite oxide was added to 50 mL DMF, stirred for 10 min, and then sonicated for 10 min; an equimolar 0.2 mol / L zinc ion solution of Zn(NO3)2·6H2O was added to the dispersion, sonicated for 20 min, and stirred for 5 min;

[0051] Dissolve 0.8 mol / L 2-methylimidazole in 50 mL of DMF and stir until clear. Mix the two in a three-necked flask and stir in an oil bath at 50°C for 18 h to obtain a gray precipitate. Centrifuge and wash three times with DMF:ethanol:water = 1:2:2 alternating solutions. Dry at 60°C for 12 h to obtain a composite powder.

[0052] Example 2 (Preparation of Metal Anticorrosion Coating)

[0053] Epoxy resin E44 and butyl acetate were mixed in a ratio of 3:1 to prepare an epoxy solution. The ZIF-8 / GO powder optimized in Example 1 was added thereto at 0.25 wt% and 1 wt%, respectively. The mixture was stirred at 200 rpm for 15 min and degassed to obtain a uniform coating. The coating was then applied to a steel plate with a wet film thickness of approximately 100 μm. After curing at 80°C for 2 h, a neutral salt spray test was performed.

[0054] Three groups of sample coatings were tested, totaling 12 specimens, as detailed in Table 1. Sample 1 consisted of a 140 μm coating with the composition shown in Example 2. Sample 2 consisted of a 120 μm epoxy zinc-rich (60%) primer, a 120 μm epoxy micaceous iron intermediate, and an 80 μm polyurethane topcoat. Sample 3 consisted of a 70 μm inorganic silicate zinc-rich primer, a 70 μm epoxy iron oxide red sealer, a 70 μm epoxy micaceous iron intermediate, and an 80 μm polyurethane topcoat.

[0055] Table 1. Neutral salt spray test comparison

[0056]

[0057] The Q235 steel plate specimens with a prefabricated size of 100mm×80mm×8mm were derusted, with a surface treatment grade of Sa2.5 and a surface roughness of 40-70μm. The specimens were polished smooth with 1200-grit sandpaper to remove oil stains and metal powder from the surface of the components. The paint was evenly applied to the surface of the specimens, requiring no gaps or leaks. After painting, the specimens were air-dried and then placed at room temperature for curing. The prepared specimens were placed in a salt spray chamber with the temperature in the chamber controlled at (40±2)℃. The pH value of the acidic salt spray test was 2-2.5, the pH value of the alkaline salt spray test was 11-11.5, and the spray volume was 3-4mL / h.

[0058] Acid resistance test results: ①1260h, the sample plates did not change, sample 1 showed no obvious phenomenon after scratching, sample 2 had 2mm of blistering and brown rust appeared at the scratch, sample 3 had 1mm of rust and blistering at the scratch; ②1560h, sample 1 had rust and blistering at the scratch, and the rust and blistering was 1mm, the rust and blistering of sample 2 and sample 3 expanded to 8mm and 5mm respectively; ③2050h, sample 2 had 18mm of rust and 6-level blistering at the scratch, the rust and blistering of sample 1 and sample 3 increased to 3 and 10mm respectively; ④3000h, sample 1 had 5mm of rust and blistering at the scratch, sample 2 had 25mm of rust and 8-level blistering at the scratch, the sample 3 flat plate had 4-level powdering, 10mm of rust and 6-level blistering at the scratch.

[0059] Results of alkali resistance test: ①1260h, all sample plates showed no change, yellow rust bubbles of 3mm appeared at the scratched area of ​​sample 2, and no obvious phenomenon appeared at the scratched area of ​​sample 3; ②1560h, 2 rust spots appeared on sample 1, the rust and peeling area of ​​sample 2 expanded, blistering of 10mm, and level 2 powdering occurred on sample 3; ③2050h, the number of rust and blistering points at the scratched area of ​​sample 1 increased to 5, the number of rust and blistering at the scratched area of ​​sample 2 increased to 19mm, and level 4 powdering occurred at the scratched area of ​​sample 3; ④3000h, 5 rust and blisters appeared at the scratched area of ​​sample 1, and black rust appeared in some of the blistering areas. Scratched area of ​​sample 2 showed large area of ​​black corrosion, and scratched area of ​​sample 3 showed large area of ​​black corrosion.

[0060] Under the acid salt spray resistance test conditions, samples 2 and 3 first showed blistering and rusting at the scratched parts, while sample 1 eventually only showed blistering and rusting at the scratched parts. The flat specimen of sample 3 showed powdering, and the scratched specimen showed powdering, rust and blistering.

[0061] Under the alkaline salt spray resistance test conditions, sample 1 only had partial black rust at the blistering position after being scratched, while samples 2 and 3 had large areas of rust after being scratched.

[0062] In summary, it can be seen that the acid and alkali resistance of the anti-corrosion coating of Sample 1 of the present invention is stronger than that of the traditional anti-corrosion coatings represented by Samples 2 and 3.

[0063] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.

Claims

1. A composite powder, characterized in that: Include: Zeolite-like metal-organic frameworks are self-assembled by divalent zinc ions and imidazole organic ligands. Graphite oxide, with a degree of oxidation of 35 to 45 at%; The zeolite-like metal organic framework and the graphite oxide are compounded by in-situ self-assembly to form a composite powder with a stable pore structure, barrier properties and self-repairing function.

2. The composite powder according to claim 1, characterized in that The mass ratio of the zeolite-like metal organic framework to graphite oxide is 1:0.5 to 1:

5.

3. The composite powder according to claim 1, characterized in that The crystal size of the zeolite-like metal organic framework is 50 to 200 nm; and / or, The average sheet size of the graphite oxide is 0.5 to 5 μm; and / or, The specific surface area of ​​the composite powder is not less than 600m 2 / g.

4. The composite powder according to claim 1, characterized in that The imidazole organic ligand is selected from 2-methylimidazole or a substituted imidazole thereof; The oxygen functional groups contained in the graphite oxide are selected from hydroxyl groups, epoxy groups or carboxyl groups, and the total content of the oxygen functional groups is 20 to 45 wt %.

5. A method for preparing the composite powder according to any one of claims 1 to 4, characterized in that: The following steps are involved: dispersing graphite oxide in a suitable solvent to prepare a dispersion; preparing a divalent zinc salt solution and an imidazole organic ligand solution in a suitable solvent to obtain a zinc ion solution and a ligand solution; The dispersion, zinc ion solution and ligand solution are mixed and an in-situ self-assembly reaction is carried out in the same reaction system, so that the divalent zinc ions and the imidazole organic ligands are assembled on the surface of the graphite oxide to form a zeolite-like metal organic framework and composite with the graphite oxide; The reaction products are separated, washed and dried to obtain a composite powder with a stable pore structure, barrier properties and self-repairing function.

6. The preparation method according to claim 5, characterized in that The solvent is N,N-dimethylformamide, ethanol, water or a mixed solvent thereof; and / or, Graphite oxide is added to a solvent at 0.1 to 10 wt %, and is ultrasonically treated for 5 to 15 minutes to obtain uniform dispersion; and / or, The zinc ion solution is prepared from zinc nitrate, zinc acetate or zinc chloride, with a concentration of 0.05 to 0.5 mol / L; and / or, The ligand solution is prepared from 2-methylimidazole or a substituted imidazole thereof, with a concentration of 0.1 to 1.0 mol / L; and / or, Mixing the dispersion, zinc ion solution and ligand solution in a mass ratio of 1:(0.1-1):(0.5-5); and / or, The in situ self-assembly reaction is carried out at 50-70° C. and normal pressure for 18-24 hours.

7. A metal anticorrosion coating composition, characterized in that: include: Epoxy solution, prepared from epoxy resin; The composite powder according to any one of claims 1 to 4 or the composite powder prepared by the preparation method according to claim 5 or 6, wherein the content of the composite powder is 0.25 to 5 wt% based on the total mass of the coating composition.

8. A method for preparing the metal anticorrosion coating composition according to claim 7, characterized in that: The following steps are involved: Mixing epoxy resin and organic solvent in a container at a mass ratio of 2:1 to 4.5:1 to prepare a uniform epoxy solution; adding the composite powder to the epoxy solution to obtain a uniform mixed solution; The mixed liquid is subjected to a degassing treatment to obtain the metal anti-corrosion coating composition.

9. The preparation method according to claim 8, characterized in that The method further comprises adding a curing agent after the epoxy solution is prepared, wherein the mass ratio of the curing agent to the epoxy resin is 0.5:1 to 1.5:

1.

10. A metal anticorrosion method, characterized in that: include: The metal anticorrosion coating composition according to claim 7 is evenly applied to the surface of the metal substrate to be protected by brushing, spraying or dipping at a wet film thickness of 50-200 μm, wherein the metal substrate is steel, aluminum alloy or magnesium alloy; It is then cured at 80-120°C for 1-3 hours to form an anti-corrosion coating with a stable pore structure, barrier properties and self-repairing function.

Citation Information

Cited By

  • Aluminum-based quick-setting inorganic multi-compound gelling agent and preparation method thereof

    CN121159171A

  • Aluminum-based rapid-setting inorganic multi-component gelling agent and its preparation method

    CN121159171B

  • High solid epoxy paint and method for preparing the same

    CN122356951A

  • Zif-67@silane coupling agent modified hydroxyapatite nanowire self-repairing epoxy resin anticorrosive coating and preparation method thereof

    CN122465462A